Internalisasi Nilai Karakter Cinta Tanah Air Dalam Mencegah Radikalisme Pada Mahasiswa di Universitas Islam Jember - Anshori, Moch. Afif; Muhith, Abd; Mas'ud, Mas'ud (Pendidikan Islam Pascasarjana IAIN Jember, 2023)
The internalization of the character value of love for homeland is meant to unify differences and the spirit of love of country to bring together all groups, regardless of their culture, ethnicity, customs, and religion. However, violent incidents in the name of religion have frequently emerged and are known as radicalism in Indonesia. In response to this threat, the student council of Universitas Islam Jember, supported by the students and the rector, declared the campus anti-radicalism, stating that this declaration manifests their love for the country. For Universitas Islam Jember campus members under the auspices of the Nahdatul Ulama education foundation, the Unitary State of the Republic of Indonesia and the Pancasila ideology are non-negotiable principles. To analyze and describe the stages of internalizing the character values of love of country in preventing radicalism at the Islamic University of Jember. This research uses a qualitative approach, producing descriptive data in written or spoken words and observable behaviours about internalizing character values of love of country in preventing radicalism. The results of this study show that the character value of love of country is embodied in the rules of the campus institution under the auspices of the Nahdatul Ulama foundation, the campus vision and mission that are not only for Ahlussunnah Wal Jama'ah An Nahdliyah, but also have a high commitment to upholding Pancasila and the 1945 Constitution, strengthening the love of country through PKKBM, seminars, and general courses, applying love of country through ceremonial events such as Independence Day, National Student Day, national recitation, and so on, singing national anthems and hubbul wathan in every important event or activity, displaying photos of the president, vice president, Garuda, and the campus and department vision and mission in every classroom, and declaring Universitas Islam Jember as an anti-radicalism campus. With the character value of love of country embedded and continuously reinforced, there is no room for radicalism to grow and develop. This is because everything applied and practised at the Universitas Islam Jember campus is contrary to the characteristics or indicators of radicalism.